Effect of salinity on the survival and development of mud crab, Scylla Serrata Zoea. - Vengano, Emma Lou Lacatan
Survival and metamorphosis of five zoeal stages of Scylla serrata larvae hatched and reared at 32 ppt and abruptly transferred to salinities of 12, 16, 20, 23, 28 and 32 ppt. were detemined and compared. The effect of the salinity on survival and metamorphosis was monitored at 0, 1st, 3rd, 6th, 12th, 24th, 48th and 72nd hours. Salinity range that could be tolerated by the zoeae in each zoeal stage was also determined., Results showed that after 72 hours of exposure, Z1 abd Z2 larvae were able to tolerate abrupt transfer to salinity range of 20-32 ppt. with 70-74.4 and 61.1-72.2 survival respectively. Zoea 3 larvae could tolerate a narrower salinity range of 24-32 ppt. with survival of 50-60 even after 72 hours of exposure. Larvae at Zoea 4 and Zoea 5 stages were able to tolerate salinity range of 20-32 ppt. with survival of 80-91 and 75.6-94.4 respectively after 72 hours of observation. Death occured on the 12th hour at Z1, 48th hour at Z2, 24th hour at Z3 and Z4 and 1.1 of the larvae were remained at Z5 stage. Salinity of 16ppt. was able to suport survival of few larvae. Metamorphosis was highest at 32 ppt. in all zoeal stages except in Zoea 1 where highest number of larvae that metamorphosed was at 28 ppt. (53.3). At lower salinity levels (20-24 ppt) only a few larvae metamorphosed. At salinity level of 16 ppt. metamorphosis did not take place in Z1, Z3 and Z5 while at Z2 and Z4, 23.3). At lower salinity levels (20-24 ppt) only a few larvae metamorphosed. At salinity level of 16 ppt. metamorphosis did not take place in Z1, Z3 and Z5 while at Z2 and Z4, 23.3 and 6.7 of the larvae metamorphosed respectively.